Estimating crop-specific production technologies in Chinese agriculture: a generalized maximum entropy approach - Zhang, Xiaobo; Fan, Shenggen (Wiley, 2001)
A generalized maximum entropy approach is adapted to empirically estimate crop-specific production technologies in Chinese agriculture. Despite a modest behavioral assumption about equal marginal returns of nonland inputs among crops, this method does not require price information, which is usually distorted in a centrally planned economy such as China. A multi-output technology for Chinese agriculture is estimated and input allocations for each province are recovered simultaneously. The estimated multi-output production technology and input allocations imply that China may have greater grain production potentials than previously thought.